2019
DOI: 10.1002/vnl.21719
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, mechanical property, and processing thermal stability of PVC/La‐OMMTs nanocomposites prepared viain situintercalative polymerization

Abstract: Poly(vinyl chloride) (PVC) nanocomposites were prepared via an in situ intercalative suspension polymerization of vinyl chloride with four organic carboxylic acid salts (montmorillonite [MMT] units) containing thermally stable lanthanum ions. The effects of different lanthanum organic montmorillonites (La‐OMMTs) on the particle features and molecular weight were investigated. The transmission electron microscopy data indicated the formation of partially exfoliated or intercalated PVC/La‐OMMTs nanocomposites. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…It is found that the final achieved average grain size is influenced by the type and the concentration of particles. 2,24,44 It can be observed that, Sauter mean diameter of the final PVC grains shows an upward trend versus the percentage of dispersed particles. This is explicable by the fact that the pre-dispersion of the particles into the monomer causes an increase in the viscosity of the organic phase, thereby facilitating the coalescence and preventing the breakup.…”
Section: Polymers and Polymer Composites 29(9s)mentioning
confidence: 96%
See 1 more Smart Citation
“…It is found that the final achieved average grain size is influenced by the type and the concentration of particles. 2,24,44 It can be observed that, Sauter mean diameter of the final PVC grains shows an upward trend versus the percentage of dispersed particles. This is explicable by the fact that the pre-dispersion of the particles into the monomer causes an increase in the viscosity of the organic phase, thereby facilitating the coalescence and preventing the breakup.…”
Section: Polymers and Polymer Composites 29(9s)mentioning
confidence: 96%
“…However, its low heatsoftening temperature and poor toughness and limit its application as a kind of engineering plastics. [1][2][3][4][5] In recent years, the use of inorganic particles dispersed in a PVC matrix to provide high-performance novel materials has attracted intense interest lately from academic and industrial researchers. 6 Among nanofillers, the layered double hydroxides (LDHs) are one of the most specific inorganic fillers that have been used extensively in polymer nanocomposite preparation.…”
Section: Introductionmentioning
confidence: 99%
“…As we known, different morphologies and sheet sizes of LDHs could significantly affect the thermal stability, smoke-suppression, and mechanical properties of PVC nanocomposites [29,30]. Based on this contribution, the thermal degradation behavior of PVC-LaLDHs nanocomposites was investigated using TGA, as shown in Figure 3 and Table 1.…”
Section: Thermal Stability Performance Of Pvc-laldhs Nanocompositesmentioning
confidence: 99%
“…Thus, the PVC-LaLDHs2 exhibits satisfying strength and toughness. It is supposed that appropriate amount of La ions in composites can catalyze and generate complex with PVC [22,29,32], which increase tensile strength and elastic modulus with little affecting elongation at break of PVC. As La 3+ / Al 3+ molar ratio increases to 1 / 5, PVC-LaLDHs4 still shows obvious ductile fractured characteristics but agglomeration within the PVC matrix, implying that the dispersion between LaLDHs4 particles and PVC is poorer than that of LaLDHs2 in PVC.…”
Section: Morphological Studies Of Pvc-laldhs Nanocompositesmentioning
confidence: 99%
“…Wang, et al, 2001 made successful trial to prepare and characterize PVC/ modified montmorillonite nanocomposites using melt compounding method. Many researches have followed that to improve the resulting properties of PVC/ montmorillonite nanocomposites using melting compound method (Matuana, 2009), in situ polymerization method (Wang, et al, 2019) and solution blending method (Wang & Wilkie, 2002;Arunvisut, et al, 2007;Madaleno, et al, 2010) have studied the effect of nanosized organoclay as a filler in plastics industries. Motawie, et al, 2014 have studied the effect of nano-size organo clay on the physical and chemical properties of PVC compound.…”
Section: Introductionmentioning
confidence: 99%